ANALISIS PENERAPAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) VERSI 2.0.7. TERHADAP KINERJA PERANGKAT DESA BABAT - Luluk Maknun; Intan Ayu; Nurul Fadhilah; Sirojul Munir (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of the Village Financial System (Siskeudes) application version 2.0.7 and its impact on the performance of the Babat Village officials. The research employed a qualitative approach with data collected through in-depth interviews, observations, and documentation. The results indicate that the use of Siskeudes has brought positive changes, particularly in the speed of report preparation, accuracy of financial recording, and improvement of administrative accountability. However, challenges such as limited technological understanding among village officials and technical disruptions during system use were still encountered. Babat Village has undertaken various innovations, including proposing feature development and utilizing Siskeudes data for strategic planning. Overall, the implementation of Siskeudes 2.0.7 significantly contributes to a more effective, transparent, and accountable financial management system at the village level.